(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2026)
This study investigates the impact of interest rate changes on the demand, supply, investment behavior, and financial sustainability of business entities, using The Coca-Cola Company and PepsiCo Inc. as case studies. The analysis covers the period from 2022 to 2024 and relies on firm-level financial data obtained from official annual reports, while interest rates are represented by central bank policy rates. Demand is proxied by revenue, supply by cost of goods sold, and investment by capital expenditures, while financial pressure is assessed through interest burden and interest coverage ratios. The empirical results indicate that rising interest rates weaken demand growth over time, constrain supply expansion, and significantly increase debt-servicing pressure on firms. While demand for consumer staples remains relatively resilient, sustained high interest rates reduce investment activity and deteriorate financial flexibility, particularly for firms with higher exposure to debt financing. These findings demonstrate that interest rate changes have a measurable and economically significant effect on firm-level performance and investment decisions, highlighting the importance of monetary policy transmission at the microeconomic level.